Density and Surface Tension Measurement of Fe-Ga Melts Using Electromagnetic Levitation Technique - Adachi, Masayoshi; Higashi, Hideo; Nagakusa, Ikuma; Kawamata, Toru; Kumagai, Tsuyoshi; Fukuda, Tsuguo; Suzuki, Shigeru; Fukuyama, Hiroyuki (Tetsu to hagane, 2024)
Fe-Ga alloys are expected as a magnetostrictive material. Currently, Fe-Ga single crystals have been fabricated by the Czochralski method. Thermophysical properties of the Fe-Ga melt are necessary for the improvement of the crystal growth technique, however, these have not measured to date. The aim of this study was therefore to measure the density and surface tension of Fe-Ga melts using electromagnetic levitation technique. It is possible to measure thermophysical property of sample melts at undercooling condition using the electromagnetic levitation method. The density and surface tension of the Fe-Ga decreased with increasing temperature including supercooling temperature region. The molar volume of the Fe-Ga melt is smaller than the molar volume calculated assuming ideal solution. The surface tension of the Fe-Ga melt was in good agreement with the surface tension calculated from Butler model.